SILVER COMPLEXES FOR TUBERCULOSIS TREATMENT: A SHORT REVIEW - Biagioni, Bruno Torquato; Cavicchioli, Maurício [UNESP]; Massabni, Antonio Carlos [UNESP] (Sociedade Brasileira de Quimica (SBQ), 2022)
This paper is a brief review of silver complexes that have been identified as antibacterial drugs with promising use for the treatment of tuberculosis (TB). This treatment aims to cure and discontinue the transmission of the disease. The excessive and inappropriate use of drugs has jeopardized the effectiveness of antibiotics for the TB treatment, bringing bacterial resistance to them. To achieve these objectives, the drugs used must be able to eliminate rapidly the bacterial population, avoiding the selection of drug-resistant strains and preventing its recurrence. The number of new cases of multidrug-resistant TB (MDR-TB) and extensively drug-resistant TB (XDR-TB) continues to rise. So, it is important to develop more research to introduce new drugs or improve existing ones, which can reduce the treatment time, increasing drug adherence and reducing MDR-TB and XDR-TB. The Ag(I) complexes were described with different types of ligands, and bonds to Ag(I) occur by N, O, P, and S atoms. Metal complexes are presented as options for anti- TB treatments. There are no cases of TB treatments using metal complexes but research in this area show that they could be used in the future to eradicate the bacteria that contaminate environments, surgical materials and other objects.
Keywords: Drugs; Mycobacterium tuberculosis; Silver(I) compounds